Red de fincas agroturísticas como alternativas de emprendimiento para el turismo rural del cantón Bolívar - Muñoz Napa, Haminton David (2021)
The purpose of this study was to design a model for the management of agrotourism farms to promote rural development in the Bolívar canton. The research begins with a characterization of the territory, assessing its potential for the development of agrotourism activities under a multidimensional analysis, as well as the offer of tourist attractions and resources for the development of rural tourism. Subsequently, a circuit was designed that covered a total of 5 tourist agricultural farms which were combined with the main complementary resources of the canton, previously an inventory of the farms was carried out and their potentiality was evaluated. Two surveys were applied, one directed to the entrepreneurs of the farms through which the lack of support from public institutions was found; the second was directed to the potential demand to determine the agrotourism activities with the greatest potentiality, 4 were found as those with the highest potentiality. A bank of potential activities is proposed for each tourist site as a basis for generating tourist packages. In the last phase, a model was developed for the management of agrotourism farms based on the proposal of Félix (2020) that consists of 4 phases (trainer, consultant, operator, and promoter), 7 actions were added for its implementation and a monitoring and control plan with 9 indicators and means of verification. It is concluded that the model will serve for the development of a network of agrotourism farms for rural tourism in the Bolívar canton.